Determining Factors in the Influx of Foreign Direct Investment to Sudan: Implementing Autoregressive Distributed Lag (ARDL) - Bashir, Mohamed Sharif; Ibrahim, Ahmed Abdu Allah (Journal of Management, Economics, and Industrial Organization, 2023)
The purpose of this study was to examine foreign direct investment (FDI) in the context of Sudan between the years 1990 and 2020 by using the bounds testing method of cointegration and the error-correction model. As per the results, it can be understood that the variables considered for the study are combined on a long-term basis if FDI remains a dependent variable. Further, a significant equilibrium correction was found, which supports the existence of a long- term relationship. A number of internal and external factors especially gross domestic product (GDP), trade openness, inflation, exchange rate, and growth rate, as well as additional macroeconomic indicators such as investment/GDP) were found to impact the state of FDI in Sudan. The variables showed no causalities as per the outcomes of the Granger causality test. Moreover, as per the variance decomposition results, the forecast error variance of FDI, in addition to that of GDP, investment/GDP, and inflation, was found to be self-explanatory. Additionally, as per the impulse response functions, the results demonstrated a short-term negative association between GDP and FDI, suggesting that Sudan possesses inadequate absorptive capacity for promoting its economy using FDI. The results of this research emphasized how selective public policies can be utilized to promote FDI and consequently facilitate short- and long-term economic growth. Therefore, it is useful to recommend some policy implications to promote the application of FDI in Sudan.
Keywords: ARDL; FDI; exchange rate; economic growth; trade openness